ON MULTIPHASE ALGORITHM FOR SINGLE VARIABLE EQUATION USING NEWTON'S CORRECTION METHOD (Journal of Sciences, Islamic Republic of Iran)
This paper brings to light a method based on Multiphase algorithm for single variable equation using Newton's correction. Newton's method is derived through the logarithmic differentiation of polynomial equation. A correction term which enhances the high speed of convergence is hereby introduced. A translation of Newton's method to Total Step and Single Step Methods (T. S. M and S. S. M) respectively, forms the peak of discussion. Our method, so derived, is also discussed in the light of numerical evidence